2004
DOI: 10.17705/1jais.00044
|View full text |Cite
|
Sign up to set email alerts
|

Web Site Delays: How Tolerant are Users?

Abstract: Web page loading speed continues to vex users, even as broadband adoption increases. Several studies have addressed delays in the context of Web sites as well as interactive corporate systems, and have recommended a wide range of "rules of thumb." Some studies conclude that response times should be no greater than 2 seconds while other studies caution on delays of 12 seconds or more. One of the strongest conclusions was that complex tasks seemed to allow longer response times. This study examined delay times o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
112
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(120 citation statements)
references
References 59 publications
7
112
0
1
Order By: Relevance
“…A five second delay was guided by the literature as a reasonable value to stimulate a change in user behaviour. Studies have shown that even a small increase in query response delay can impact user behaviour [6,30], while 'acceptable' delay times for document downloading ranged from three to ten seconds [10], with work by Galletta et al [15] showing that a document download delay higher than four seconds can lead to a change in behavioural attitudes towards a webpage.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A five second delay was guided by the literature as a reasonable value to stimulate a change in user behaviour. Studies have shown that even a small increase in query response delay can impact user behaviour [6,30], while 'acceptable' delay times for document downloading ranged from three to ten seconds [10], with work by Galletta et al [15] showing that a document download delay higher than four seconds can lead to a change in behavioural attitudes towards a webpage.…”
Section: Methodsmentioning
confidence: 99%
“…These delays have been shown as a source of major frustration to users [7]. Indeed, several studies have examined the e↵ect of page loading delays in the context of browsing the web [15,25]. It has been shown that the longer a page takes to load, the less favourably users see that page when it finally appears [28].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The sharing of resources by such applications owned by multiple customers raises new resource allocation challenges such as ensuring responsiveness under dynamically changing workloads and isolating them from demand fluctuations in co-located virtual machines (VMs). However, despite the well-documented importance of responsiveness to end users [1,2,3], cloud services today typically only address availability guarantees and not response-time-based service level agreements (SLAs).…”
Section: Introductionmentioning
confidence: 99%